Thermodynamic Studies of the Molecular Interactions of 2,4-Dichlorophenol and 2,4,6-Trichlorophenol with Free Bases meso-Tetraarylporphyrins - ZABARDASTI, ABEDIEN; FARHADI, SAEID; REZVANI ABKENARI, ZOYA (Asian Journal of Chemistry, 2010)
The hydrogen bonded complexes of 2,4-dichlorophenol (2,4- DCP) and 2,4,6-trichlorophenol (2,4,6-TCP) with free base mesotetraarylporphyrins [H2T(4-X)PP] (X = OCH3, CH3, H, Cl) have been studied. The formation constants K and other thermodynamic parameters were calculated by UV-Vis spectrophotometry titration method. The formation constants show the following trend relative to X substituent of porphyrins: H2T(4-CH3O)PP > H2T(4-CH3)PP > H2TPP > H2T(4-Cl)PP On the other hand, formation constants show that 2,4-DCP form more stable hydrogen bonded complexes than 2,4,6-TCP with free base porphyrins.